2019
DOI: 10.24972/ijts.2019.38.1.99
|View full text |Cite
|
Sign up to set email alerts
|

The religious and philosophical characteristics in a consensually nonmonogamous sample

Abstract: Consensual nonmonogamy refers to the variety of ways people partner romantically and/or sexually with multiple others. This study examined the spiritual identities of people who self-identify as consensually and openly partnered with more than one person, as well as if and how these identities changed since childhood. Moreover, to deepen previous transpersonal research that investigated how nonmonogamous paradigms of loving contribute to spiritual development, the study also examined between group differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some studies found no association between engagement in CNM and demographic factors such as age, gender, race/ethnicity, socioeconomic status, sexual orientation, religious and political affiliation, and geographical location (Haupert et al, 2017; Lecuona et al, 2021; Moors, Gesselman, & Garcia, 2021; Rubin et al, 2014; Sizemore & Olmstead, 2017a; St. Vil et al, 2021). Other studies found that people who are White, younger, sexual minorities, men, nonbinary, transgender, and those who have more liberal political and religious views are more likely to engage in CNM and polyamory than their counterparts (Balzarini, Dharma, Kohut, Holmes, et al, 2019; Breslow et al, 2021; Cunningham et al, 2022; Kimberly & McGinley, 2019; Kolesar & Pardo, 2019; Levine et al, 2018; Moors, Gesselman, & Garcia, 2021; Wilt et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found no association between engagement in CNM and demographic factors such as age, gender, race/ethnicity, socioeconomic status, sexual orientation, religious and political affiliation, and geographical location (Haupert et al, 2017; Lecuona et al, 2021; Moors, Gesselman, & Garcia, 2021; Rubin et al, 2014; Sizemore & Olmstead, 2017a; St. Vil et al, 2021). Other studies found that people who are White, younger, sexual minorities, men, nonbinary, transgender, and those who have more liberal political and religious views are more likely to engage in CNM and polyamory than their counterparts (Balzarini, Dharma, Kohut, Holmes, et al, 2019; Breslow et al, 2021; Cunningham et al, 2022; Kimberly & McGinley, 2019; Kolesar & Pardo, 2019; Levine et al, 2018; Moors, Gesselman, & Garcia, 2021; Wilt et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Vil et al, 2021). Other studies found that people who are White, younger, sexual minorities, men, nonbinary, transgender, and those who have more liberal political and religious views are more likely to engage in CNM and polyamory than their counterparts Breslow et al, 2021;Cunningham et al, 2022;Kimberly & McGinley, 2019;Kolesar & Pardo, 2019;Levine et al, 2018;Moors, Gesselman, & Garcia, 2021;Wilt et al, 2018).…”
Section: Antecedents Of Cnmmentioning
confidence: 99%